2009
DOI: 10.3892/or_00000381
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of telomere-related proteins correlates with resistance to radiation in human laryngeal cancer cell lines

Abstract: Abstract.Telomere-associated proteins function as survival factors in telomere maintenance, which are major contributors to radiosensitivity in human cancers. The aim of this study was to investigate the association of telomere-associated gene expression and radiation resistance in human larynx squamous carcinoma. The changes of telomere-associated gene expressions and bionomical characteristics that occur in two human larynx squamous carcinoma cell lines (Hep-2 and Hep-2R), with different radiosensitivities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In our previous study, we found that GLUT-1 is expressed at high levels in a Hep-2 laryngeal cancer cell line expressing high levels of CD133 (CD133 + -Hep-2),26 and GLUT-1 siRNA improved the radiosensitivity of CD133 + -Hep-2 cells. There have been other studies on radioresistant Hep-2 (Hep-2R) 27,28. However, the correlation between high-level GLUT-1 expression and radioresistance in Hep-2R cells expressing high levels of CD133 (CD133 + -Hep-2R) has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that GLUT-1 is expressed at high levels in a Hep-2 laryngeal cancer cell line expressing high levels of CD133 (CD133 + -Hep-2),26 and GLUT-1 siRNA improved the radiosensitivity of CD133 + -Hep-2 cells. There have been other studies on radioresistant Hep-2 (Hep-2R) 27,28. However, the correlation between high-level GLUT-1 expression and radioresistance in Hep-2R cells expressing high levels of CD133 (CD133 + -Hep-2R) has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%